WHEN CLITIC SYSTEMS COLLIDE, ANIMACY, FOR THE MOST PART, BEATS GENDER - Schmitt, Cristina; Primucci, Ana Eleonora; Munn, Alan; Brandani, Lucia; Avellana, Alicia (Estudos Linguísticos e Literários, 2024)
In this paper we present elicitation results from an experiment on the acquisition of 3rd person object clitics by children of Paraguayan parents living in Buenos Aires and their mothers. These children are immersed in a situation of contact between two varieties of Spanish: the Paraguayan system (∅ for inanimate objects and LE for animate objects) and the local Argentinian system which uses LO for Masculine and LA for Feminine clitics. Results show that the Paraguayan mothers use substantially more LO/LA when compared with adults in Paraguay, as described by Choi (2000), suggesting a great deal of attrition. Their children on the other hand use far less LO/LA, but at the same time are not adopting as a group a LE/∅ system. Examining 19 Mother/Child dyads, we find that no children are exclusively using LO/LA users but some children are exclusively using LE/∅. As for mother we find some LO/LA users and the rest uses a mixed system. Interestingly, overall children use fewer forms than mothers.